2010
DOI: 10.1007/s10552-010-9585-7
|View full text |Cite
|
Sign up to set email alerts
|

A remarkable reduction of breast cancer deaths in screened versus unscreened women: a case-referent study

Abstract: Screening resulted in a remarkable reduction in breast cancer mortality. Contrary to findings in other countries, adjustment for self-selection in Limburg had no influence on the impact of screening. Thanks to a well-organized centralized screening program, similar results are expected in other regions of the Netherlands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 26 publications
1
41
0
1
Order By: Relevance
“…Our estimated correction factor of 1.11 (95% CI, 0.99-1.25) for the Southwest region was comparable with the estimate reported by Puliti and colleagues (6), 1.11 (95% CI, 0.87-1.40) but higher than that recently applied for the South Dutch region, 0.84 (95% CI, 0.58-1.21; ref. 30) and suggests higher risk of breast cancer among nonparticipants in the Southwest region. The issue of analysis by stratification on risk has been addressed earlier by Elmore and colleagues (27).…”
Section: Discussionmentioning
confidence: 99%
“…Our estimated correction factor of 1.11 (95% CI, 0.99-1.25) for the Southwest region was comparable with the estimate reported by Puliti and colleagues (6), 1.11 (95% CI, 0.87-1.40) but higher than that recently applied for the South Dutch region, 0.84 (95% CI, 0.58-1.21; ref. 30) and suggests higher risk of breast cancer among nonparticipants in the Southwest region. The issue of analysis by stratification on risk has been addressed earlier by Elmore and colleagues (27).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the randomized controlled trials 5,12 , numerous observational studies show a marked decline in breast cancer deaths for women screened in their 40s [13][14][15][16][17][18] . The data are equally as strong (if not stronger) for women 40-49 years of age as for older women, and women in their 40s have more years of life to lose.…”
Section: The Panels Provide Contradictory Analyses At What Age Shouldmentioning
confidence: 99%
“…On the other hand, numerous studies show that screening results in declining deaths [14][15][16][17][18][19][27][28][29][30][31][32][33][34][35] , separate from access to therapy.…”
Section: Claimed Contribution Of Improvements In Therapymentioning
confidence: 99%
“…1 We never stated that our study "proves" that screening saves lives; proof is derived from randomized controlled trials, including those beginning at age 40 years, and is confirmed by numerous observational studies. [2][3][4][5][6][7][8][9][10][11][12][13] There is no scientific rationale for the use of age 50 years as a threshold.…”
Section: Reply To a Failure Analysis Of Invasive Breast Cancer: Most mentioning
confidence: 99%